Acute cyanide poisoning by subcutaneous injection. Issue 5 (20th April 2005) - Prieto, I; Pujol, I; Santiuste, C; Poyo-Guerrero, R; Diego, A
Abstract : A 30 year old woman with a history of depression and previous suicide attempts was brought to the emergency department in coma. She had injected herself with cyanide subcutaneously and had severe metabolic acidosis. She underwent sustained haemodialysis in the intensive care unit (ICU) before laboratory confirmation of cyanide poisoning. The serum cyanide concentration was 4.6 μg/ml. After 48 hours the patient, now asymptomatic, was discharged from the ICU.